Synthesis, swelling and morphological properties of tea waste-based ydrogel as a slow-release NPK fertilizer applied to eggplant seed germination and growth - Wan Amirah Najwa, Wan Anuar; Ros Azlinawati, Ramli; Yuen, Mei Lian; Rodziah, Nazlan; Tan, Suat Hian; Rasidi, Roslan (Springer, 2026)
Incorporating tea waste (TW) into hydrogel systems promotes sustainability and supports the principles of circular economy. A tea waste-grafted-polyacrylic acid/NPK (TW-g-PAA/NPK) slow-release fertilizer hydrogel (SRFH) was developed and compared with a polyacrylic acid (PAA) superabsorbent polymer (SAP) and TW-g-PAA superabsorbent polymer composite (SAPC). FTIR, SEM, and SEM–EDX analyses confirmed successful grafting, evidenced by a characteristic peak shift to 1046 cm⁻1, and verified the presence of N, P, and K in SRFH. The SRFH exhibited the smallest pore size, lowest grafting efficiency (110%), yet highest mechanical strength (9.80 MPa compressive resistance) among the hydrogels. It also showed the lowest water absorbency capacity, leading to a slower release rate, but maintained excellent reswelling ability over five cycles. Soil burial tests demonstrated SRFH's superior biodegradability (~ 80% weight loss in six weeks). In agricultural tests, SRFH-treated soil promoted the fastest germination and best growth of mini eggplant seeds. This work presents an eco-friendly, high-performance hydrogel fertilizer that enhances nutrient release, water retention, and mechanical durability for practical agricultural applications. Compared with previously reported hydrogel systems, the incorporation of TW improves cost-efficiency, network density, and swelling resilience. These findings advance the development of sustainable,high-performance hydrogels, offering practical insights for the polymer research community and real-world agricultural use.